Utilization of Dicotyledonous Medicinal Plants in The Wailaboha Forest, Central Sumba Regency, as A Learning Resource in The Form of an Encyclopedia - Day, Aply Rambu; Makaborang, Yohana; Ina, Anita Tamu (Biosfer: Jurnal Tadris Biologi, 2022)
This study aimed to find out how dicotyledonous medicinal plants were used in the Wailaboha Forest, Central Sumba Regency, and to use the research findings as a learning resource in the form of an encyclopedia. The descriptive quantitative technique was utilized. The subjects of this study were all dicotyledonous plants identified in the Hutan Wailaboha Kecamatan Umbu Ratu Nggay region. The samples in this study were dicotyledonous medicinal plants collected utilizing purposive sampling techniques at each research location. The double plot approach and observation plots were utilized to collect data in this investigation. This study's data analysis techniques were Relative Density, Relative Frequency, Significance Index, and Shannon-Wiener Diversity Index. At the same time, the validation team, including the head of MGMP and biology teachers in Central Sumba, assessed learning resources. The encyclopedia validation test yielded 98% for validator I, 89% for validator II, and 75% for validator III. This value suggests that the encyclopedia is usable and can help with learning.ABSTRAK:. Tujuan penelitian ini yaitu untuk mengetahui pemanfaatan tumbuhan obat dikotil di Hutan Wailaboha Kabupaten Sumba Tengah dan menjadikan hasil penelitian sebagai sumber belajar dalam bentuk Ensiklopedia. Metode yang digunakan adalah metode deskriptif kuantitatif. Subyek penelitian ini terdiri dari semua jenis tumbuhan dikotil yang terdapat dikawasan Hutan Wailaboha Kecamatan Umbu Ratu Nggay . Sampel dalam penelitian ini terdiri dari tumbuhan obat dikotil yang terdapat di setiap stasiun penelitian dengan menggunakan teknik purpose sampling. Teknik pengumpulan data dalam penelitian ini menggunakan metode petak ganda dan plot pengamatan. Teknik analisis data yang dilakukan dalam penelitian ini menggunakan Relative Density, Relative Frequency, Significance Index, dan Shannon-Wiener Diversity Index sedangkan penilaian sumber belajar dilakukan oleh tim validasi yaitu ketua MGMP dan guru-guru biologi di Sumba Tengah. Hasil uji validasi ensiklopedia oleh validator I yaitu 98%, validator II sebesar 89%, dan validator III sebesar 78,5%. Nilai tersebut menunjukkan bahwa ensiklopedia layak digunakan dan dapat menunjang proses pembelajaran.